EFFORTS TO IMPROVE LECTURER PERFORMANCE IN HUMAN RESOURCES DEVELOPMENT - Khaeruman Khaeruman; Musa Hubeis; Nancy Yusnita (Yayasan Education and Social Center, 2022)
This study aims to describe and analyze human resources' role in improving lecturers' performance at Bina Bangsa University, Banten. This study describes and analyzes the improvement of lecturer performance at Bina Bangsa University Banten using qualitative methods, data collection techniques in this study using observation, interviews, and documentation, data analysis techniques through deductive analysis, comparative analysis, and data verification, checking the validity of the findings, namely persistent observation, triangulation test, conducting checks to prove the truth of the data that researchers have found. The results of the study (1) The role of Human Resources in Improving Lecturer Performance at the University of Bina Bangsa Banten must go through a planned HR planning process, HR recruitment according to needs, HR development and development in the form of training, promotion and transfer of HR if needed, termination of HR according to performance, HR Assessment according to the evaluation results of lecturers and proper salary compensation for existing HR; (2) The performance of lecturers at the University of Bina Bangsa Banten can be seen from their ability to make lesson plans, how to manage classes according to the conditions of students so that they are comfortable in learning and carry out learning evaluations related to the mastery of a lecturer's material and the continued development of the lecturer's profession